Customer satisfaction towards traditional & complementary medicine among the community in pengkalan chepa, kelantan - Nor Syafiqah Roslan; Nur Ezatul Iranie Shuib; Nur Fakhira Izzati Faisal; Nurul Najihah Mohd Zambri (2023)
Society's culture and belief system play an important role in the perception of health, behavior and individual response to illness and treatment methods. Almost all societies in the world combine several methods in the treatment of a disease, especially the use of traditional and alternative treatment methods, as well as modern medicine. The issue of customer satisfaction with Traditional and Complementary Medicine is the most important obstacle to any medicine. A qualitative study was conducted to identify the factors that influence customers toward Traditional and Complementary Medicine in the community of Pengkalan Chepa, Kelantan. In-depth interviews were conducted with 10 respondents. The data obtained were analyzed using the content analysis method. The findings of the study show that the community in Pengkalan Chepa, Kelantan has a problem of satisfaction with this Traditional and Complementary Medicine. The findings of this study also show that the community of Pengkalan Chepa, Kelantan is aware of the importance of traditional and complementary medicine. Keywords: Customer satisfaction, Traditional and Complimentary Medicine, Treatment Effect, Service Quality, Knowledge of Treatment